UPAYA PENINGKATAN PERSEPSI PERAWATAN KAKI PASIEN DIABETES MELITUS TIPE 2: ACTION RESEARCH DI KLINIK PRATAMA 24 JAM FIRDAUS UMY - Suib Suib (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Background: Diabetic Mellitus (DM) patient rarely to obtain health education related foot care from the health services, therefore patients perceived that DM foot care is unnecessary. This study was aimed to enhance the patient’s perception on Diabetic foot care in DM type 2 in the Firdaus Primary Clinic Muhammadiyah University of Yogyakarta (UMY). Methods: Qualitative study with action research design which composed three cycles was applied to frame this study. Six of DM type 2 clients in the Firdaus Primary Clinic Muhammadiyah University of Yogyakarta (UMY) were selected to participate as respondents in this research.Results: Before received intervention, DM patients were assumed that foot care was not being required and has not performed special foot care yet. This might happen because insufficient information related the diabetic foot care.DM type 2 client have perceived that diabetic foot care was the same treatment like healthy people have. After received intervention and perform the foot care at the first cycle, the DM patients were perceived that foot care is important. They felt some foot disorder such as numb, aches and pain were decreased after performing the foot care at the second stage. Moreover, at the third cycle evaluation’s patients still conducting the foot care. Furthermore, diabetic foot care has become daily activity because they felt the advantages.Conclusion: Based on the Focus Group Discussion (FGD) analysis and interview with the DM type 2 patients found that the diabetic foot care training could improve perception related the importance and beneficence of foot care so that patients keep performing the foot care.